Evaluation of the effect of photoplethysmograms on workers’ exposure to methyl bromide using second derivative - Choi, Jungmi; Cha, Wonseok; Park, Min-Goo (Frontiers in Public Health, 2023)
Methyl bromide (MB) is worldwide the only effective fumigant heavily used for quarantine pre-shipment treatment and has a critical use exemption for soil fumigations due to its excellent permeability and insecticidal effect. However, MB should be replaced as it is an an ozone-depleting substance and also highly toxic to humans. Recently, MB has been shown to be hazardous even for asymptomatic workers, affecting their central and autonomic nervous systems. However, the effects of MB exposure on vascular health have not been explored. This study aimed to determine whether MB affects the arterial system of asymptomatic workers. We measured the second derivative of the photoplethysmogram (SDPTG) indices, which are indicators of vascular load and aging, and urinary bromide ion (Br−) concentrations in 44 fumigators (study group) and 20 inspectors (control group) before and after fumigation. In fumigators, the mean values of post-work SDPTG indices (b/a, c/a, d/a, e/a, and SDPTG aging index) and Br− levels were significantly changed compared to their pre-work values (p < 0.05), indicating a negative effect on their cardiovascular health. In contrast, SDPTG indices and Br− levels in inspectors did not show any differences before and after work. All SDPTG indices except c/a showed significant correlations with Br− levels in all individuals (p < 0.05). In conclusion, the Br− levels and SDPTG indices of fumigators varied after MB work, and they experienced negative effects on their health despite being asymptomatic.